Opioid Pharmacokinetics-Pharmacodynamics: Clinical Implications in Acute Pain Management in Trauma. (March 2016) - MacKenzie, Meghan; Zed, Peter J.; Ensom, Mary H. H.
Objective: To evaluate acute traumatic pain protocols and to suggest optimization by characterizing opioid pharmacokinetics and pharmacodynamics (PK-PD).Data Sources: MEDLINE (1946 to November 2015), EMBASE (1974 to November 2015), International Pharmaceutical Abstracts (1970 to December 2014), and Cochrane Database of Systematic Reviews (2005 to November 2015). Keywords: morphine, hydromorphone, fentanyl, trauma, acute pain, intravenous, opioid, pharmacokinetic s, and pharmacodynamics .Study Selection and Data Extraction: Literature characterizing opioid PK-PD was included. Additionally, studies evaluatingoutcomes of opioids for acute severe pain in adult trauma patients were selected.Data Synthesis: PK-PD literature suggests that morphine exhibits an effect delay of 1.6 to 4.8 hours; however, clinical significance is doubtful. The relative onset of morphine is approximately 6 minutes, and duration, 96 minutes. Morphine 0.1 mg/kg IV then 0.05 mg/kg every 5 minutes achieved pain control in 40% of patients at 10 minutes and 76% at 60 minutes. The effect delay of hydromorphone (orally) is 18 to 38 minutes; its relative onset (IV), 5 minutes; and duration, 120 minutes. Hydromorphone every 15 minutes achieved variable success in clinical trials. The effect delay of fentanyl IV is 16.4 minutes; relative onset, 2 minutes; and duration, 7 minutes. One randomized controlled trial used fentanyl 0.1 µg/kg IV every 5 minutes.Conclusions: Further integration of opioid PK-PD into acutepain protocols is possible. One opioid should not be deemed more effective but rather titrated to effect. Morphine and hydromorphone can be titrated IV every 5 minutes until adequate pain control. Fentanyl can be titrated every 3 minutes.